Precise Diagnosis and Therapy of Bone Cancer Using Near-Infrared Lights - Cai, Qing; Li, Zuntai; Li, Baosheng; Jiang, Jiayang; Li, Xiaoyu; Meng, Weiyan; Zhu, Shoujun (Frontiers in Bioengineering and Biotechnology, 2021)
Bone is a preferred site for both primary and metastasis tumors. Current diagnosis of osteopathia typically relies on noninvasive skeleton radiography technology. However, due to the limited resolution of ionizing radiation, accurate diagnosis and effective identification impairment areas are still lacking. Near-infrared (NIR) bioimaging, especially in the NIR-II (1000-1700 nm) regions, can provide high sensitivity and spatiotemporal resolution bioimaging compared to the conventional radiography. Thus, NIR bioimaging affords intraoperative visualization and imaging-guided surgery, aiming to overcome challenges associated with theranostics of osteopathia and bone tumors. The present review aimed to summarize the latest evidence on the use of NIR probes for the targeting bone imaging. We further highlight the recent advances in bone photoX (X presents thermal, dynamic, and immuno) therapy through NIR probes, in particular combination with other customized therapeutic agents could provide high-efficiency treatment for bone tumors.